TorakochirurgiaRecurrent malignant solitary fibrous tumour of the pleura – a case report of a delayed diagnosis - Gąsiorowski, Łukasz; Dyszkiewicz, Wojciech; Kasprzyk, Mariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Malignant solitary tumours of the pleura are extremely rare neoplasms usually presenting with dramatic symptoms. A 54-year- old female presented with symptoms of confusion. Chest X-ray and CT showed a huge mass in the right pleural cavity. Diagnostic thoracoscopy yielded a false result of small cell cancer. The final pathology was positive for a malignant SFT. The operative procedure required removal of the mass. The follow-up exam showed a recurrent tumour and a pneumonectomy was required for a radical resection. The postoperative course was uneventful and follow-up exam showed no recurrence of the disease.